Social Policy. - Baldock, John, 1948-; Mitton, Lavinia; Manning, Nick, 1949-; Vickerstaff, Sarah, 1956- (Oxford : Oxford University Press, 2012)
Designed for use by undergraduates on social policy, social work and sociology courses and by students on vocational training courses (including postgraduate), this textbook covers all the main topics of social policy.
Previous edition: 2007.
Includes bibliographical references and index.
Keywords: Social policy; Society; Great Britain -- Social policy -- 1979-